Pérdida de memoria a corto plazo en los estudiantes de la Unidad Educativa Rosa Zárate - Tipan Chimborazo, Douglas Xavier (2022)
This research work is aimed at a bibliographic review with different authors, whichproposes as a general objective; to analyze short-term memory loss in first and second-year high schoolstudents from the Rosa Zárate Educational Unit, through research withscientific articles. Short- term memory is itself a temporary storage and fast programming, in which said collected information is detailed, demonstrated, andestablished for later storage, where the informationis retained for a minimum period ofapproximately twenty seconds. On the other hand, short-term memory works actively,which is why it is called working memory. The research presentsa quantitative approachwith a non-experimental and descriptive design in itself, taking into account what wasanalyzed and what are the characteristics presented by the first and second high schoolstudents of the Rosa Zárate educational Unit. For data collection, first and secondhighschool students were evaluated with a population of 60 students, including men and women, where the test Developed by Gilewski, Zelinsky and Sahie, (1990) validated by Alarcón, Rubio, and Fernández was applied (2008) where it is composed of 31 items.